2010
DOI: 10.1002/jms.1750
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric discrimination and rapid analysis of underivatized lactose, maltose, and sucrose in vegetable matrices by U‐HPLC–ESI‐MS/MS using porous graphitic carbon

Abstract: Lactose intolerance is a common condition caused by intestinal lactase deficiency, and a lactose-free diet represents the simplest way to avoid gastrointestinal symptoms. The emerging use of dietary supplements requires analytical tools that are capable of assessing these analytes, particularly for those based on dry herbal extracts that contain lactose together with maltose and sucrose, because of cross-contamination and/or deliberate addition as excipient. Electrospray ionization mass spectrometry (ESI-MS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…For the analysis of this compound, the 2 peaks were summed. The separation of anomers at the reducing end is present in other separation media such as PGC (37). For this reason, oligosaccharides often were reduced to produce a single alditol at the reducing end.…”
Section: Uplc/qqq-ms Analysis Of Hmos In Mrm Modementioning
confidence: 99%
“…For the analysis of this compound, the 2 peaks were summed. The separation of anomers at the reducing end is present in other separation media such as PGC (37). For this reason, oligosaccharides often were reduced to produce a single alditol at the reducing end.…”
Section: Uplc/qqq-ms Analysis Of Hmos In Mrm Modementioning
confidence: 99%
“…Mulroney et al demonstrated that measurement of ␤-linked glucose disaccharides in the negative ion mode provided more structural information than in the positive ion mode because deprotonation of the anomeric hydroxyl causes fragmentation [12]. Recently, lactose, maltose, and sucrose in vegetable matrices were detected by U-HPLC-MS n in the negative SRM mode using only mother ions for quantification [20]. Moreover, HPLC combined with corona charged aerosol detector (CAD) was presented in the PITTCON conference as a new lactose determination method [18].…”
Section: Introductionmentioning
confidence: 98%
“…There are many other examples of artificial systems indicating an important role of carbohydrate–aromatic interactions in molecular recognition. For example, porous graphitic carbon columns can be successfully applied in the chromatography of carbohydrates, despite their high polarity [ 26 ]. Carbohydrates were also successfully used in the solubilisation of carbon-based nanomaterials such as carbon nanotubes [ 27 , 28 ] ( Figure 4 B).…”
Section: Carbohydrate–aromatic Interactionsmentioning
confidence: 99%